2017
DOI: 10.3224/zff.v29i2.01
|View full text |Cite
|
Sign up to set email alerts
|

Turning points in the transition to parenthood: Variability of father involvement over time

Abstract: "Although fathers' involvement in care work has increased, the transition to parenthood still implies a gendered division of labour. In order to gain more knowledge of this ambivalence, we focus on the variability of father involvement at this transition. Based on an Austrian qualitative longitudinal study with couples experiencing the transition to first-time parenthood, we examined how fathers' affective, cognitive and behavioural involvement varies across the transition process. Changes in fathers' involvem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 36 publications
0
6
0
Order By: Relevance
“…Concerning personal challenges, fathers identified the lack of time to carry on personal activities and the loss of personal autonomy. Hence, fathers addressed the importance of engaging in extra work and family activities, such as sports and leisure, to improve their availability to be involved (ID #6, #9, #12):
That time when I'm not working and when I'm not with family is I think very, very important to my sanity, you know, and if I didn't have that, and if I didn't make sure that I got that regardless, you know (Schmidt et al, 2017, p. 348).
…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Concerning personal challenges, fathers identified the lack of time to carry on personal activities and the loss of personal autonomy. Hence, fathers addressed the importance of engaging in extra work and family activities, such as sports and leisure, to improve their availability to be involved (ID #6, #9, #12):
That time when I'm not working and when I'm not with family is I think very, very important to my sanity, you know, and if I didn't have that, and if I didn't make sure that I got that regardless, you know (Schmidt et al, 2017, p. 348).
…”
Section: Resultsmentioning
confidence: 99%
“…That time when I'm not working and when I'm not with family is I think very, very important to my sanity, you know, and if I didn't have that, and if I didn't make sure that I got that regardless, you know (Schmidt et al, 2017, p. 348).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Fathers who are involved in Neonatal Intensive Care Unit (NICU) help to reduce length of stay, improve weight gain, and improve psychosocial behaviors at 18 months (Cabrera & Tamis-Lemonda, 2013;Dubowitz et al, 2000;Lamb, 2000;Sarkadi et al, 2008;Tikotzky et al, 2010;Wong et al, 2017) The intense parenting experience in the NICU leads to pronounced turning points for fathers. Even with healthy infants, fathering goes through crucial transformations from prenatal to postnatal times with many variations both between different fathers and in types of fathering (Schmidt et al, 2017). Jackson et al (2003) found that parents with preterm infants internalize parenting during the first 18 months of their child's life by going through alienation, responsibility, confidence, and finally, to familiarity.…”
Section: Fathering Nicu Infantsmentioning
confidence: 99%